Seasonal variation of human semen parameters: a retrospective study in Chennai, Tamil Nadu - D., Shiny Jenefa; Shankar, Kundavi; Asokan, Yamini; Veerasigamani, Geetha; Vittal, Rashmi Gingade; Naaram, Nithya M.; K. R., Hema Niveda; Devarajan, Sandhya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Infertility in humans is a prevalent disorder that arises from several primary or secondary reasons. Regarding the latter, many seasonal and meteorological trends have been proposed as potential contributors. This study set out to determine whether the functional properties of semen samples kept in a secondary centre database showed any signs of a potential seasonal trend. Methods: Retrospective analysis was performed on the 1830 consecutive sperm analysis reports that were gathered at the Institute of Reproductive Medicine and Women’s Health over the course of a year (2020-2024). Microscopic, macroscopic examinations were included in the reports. Season of sample collection was used to examine data for various parameters. The assessment of continuous variables should be done using the ANOVA test. Additionally, a regression analysis and chi-squared will be carried out to determine the significant variation caused by season on semen parameter. Results: Seasonal variations significantly impact sperm concentration and total sperm count, with temperature changes across seasons being a key factor. However, motility, morphology, and defect parameters remain stable and unaffected by temperature. Environmental factors like temperature should be considered in fertility assessments and treatments. Conclusions: In conclusion, this thesis demonstrates that semen quality is significantly influenced by seasonal variations, with cooler temperatures associated with improved sperm concentration and total count, as indicated by statistically significant p values (p<0.05) for these parameters. The p values for sperm concentration (p=0.0280) and total sperm count (p=0.0363) confirm a significant relationship with seasonal temperature changes. In contrast, parameters such as motility and morphology remain relatively stable across seasons, as evidenced by non-significant p values (p>0.05).